Reducing Poverty and Improving Food Security through Public-Private Partnerships in the Coastal Areas - Rusliadi Rusliadi; Ida Widianingsih; Rd Achmad Buchari (Journal of Contemporary Governance and Public Policy, 2024)
This study analyses the role and impact of public-private partnerships to improve food security in coastal areas of Indonesia. The public-private partnership model as a tool to address poverty, food needs and stunting is examined using a qualitative exploratory technique. Additional information was gathered by the researchers via interviews, field observations and documents. The study was carried out in Indonesia’s Coastal Takalar Regency, and NVivo 12 Pro was used to visualise the data. The results showed that the parties involved in efforts to improve food security on the Takalar Regency Coast include the Food Social Service and Village Community Empowerment of Takalar Regency, Subdistrict Social Welfare Workers, village government, Mandiri Bank, food suppliers and E-Warong (noncash government assistance) agents. Findings further showed that the benefits arising from this collaboration can reduce social inequalities such as decreasing poverty, increasing food needs and reducing stunting cases in the coastal areas of Takalar Regency. This work revealed several obstacles to cooperation between the government and the private sector to improve food security through food aid programmes, namely corruption through diversion of aid funds and a lack of supervision.